Platelet-activating factor receptor antagonists of natural origin for acute ischemic stroke: a systematic review of current evidence - Li, Tingting; Zhang, Xuebin; Jiang, Ping; Zhang, Dandan; Feng, Luda; Lai, Xinxing; Qin, Mingzhen; Wei, Yufei; Zhang, Chi; Gao, Ying (Frontiers in Pharmacology, 2022)
Abstract Background: Acute Ischemic stroke (AIS) is the main cause of death and long-term disability worldwide. Recent trials of platelet-activating factor receptor antagonists (PAFRA) appeared to indicate that its related preparations could play a neuroprotective role in the treatment of AIS. We conducted a systematic review to evaluate the clinical efficacy and safety of PAFRA in patients with AIS. Methods: A systematic literature search was performed in seven electronic databases from inception to March 11th 2022. All randomized controlled trials (RCTs) in which patients were treated with PAFRA strategies within 7 days of stroke onset were included. The review protocol was previously registered (PROSPERO CRD42020182075). Results: Fifteen RCTs comprising a total of 3907 participants were included in this study. The PAFRA-related preparations included Ginkgo Endoterpene Diester Meglumine, Ginkgo Bilobate Dropping Pill, Ginkgolide Injection, Hesperidin, Ginsenoside Rd Injection and Hydroxysafﬂor Yellow A. Treatment was associated with improved clinical outcome for: 1) GEDM, GDI and GBDP in patients treated with conventional treatment(CM) [GEDM+CM for AIS on mRS: MDmRS = -0.42, 95% CI (-0.47, -0.37),five trials, p<0.00001; GEDM+CM for AIS on NIHSS: MDNIHSS = -1.02, 95% CI (-1.51, -0.52), four trials, p<0.0001] ; 2) GEDM and GDI in patients treated with neuroprotective agent(NPA) [GEDM+NPA+CM for AIS on mRS: MDmRS =-0.40, 95% CI (-0.54, -0.26), p<0.00001; GEDM+NPA for AIS on NIHSS: MDNIHSS = -3.93, 95%CI (-7.72, -0.14), p=0.04]; 3) GBDP in patients treated with CM; 4) GDI and GSRI in patients treated with IV rt-PA therapy (IVT); 5) HSYA in patients compared with Dengzhan Xixin Injection (DZXXI). No access to improved clinical outcome was associated with HES in patients treated with IVT. Seven RCTs reported the adverse events(AEs) and found that taking PAFRA-related preparations was not associated with an increased incidence of AEs. Conclusion: This systematic review could make an important contribution to the existing body of current evidence, and lay a well-conducted basis for providing opinions and recommendation on the evaluation of this PAFRA category medicine. Further research is required, using standardized functional outcome measures for AIS, adequate blinding and suitable comparator groups reflecting current best practice.